Isotope mass dependence of pedestal transport in JET H-mode plasmas. (1st March 2023) - Predebon, I.; Hatch, D.R.; Frassinetti, L.; Horvath, L.; Saarelma, S.; Chapman-Oplopoiou, B.; Görler, T.; Maggi, C.F.
Abstract: We present a comparative transport analysis of the isotope mass dependence in the pedestal of two pairs of deuterium/hydrogen type I ELMy H-mode discharges in JET with ITER-like wall, one characterized by the same input power, the other one by the same stored energy. The investigation, carried out using the gyrokinetic code GENE, focuses on the steep profile region of the pedestal. While large wavenumber modes mainly contribute to the electron heat flux and are scarcely influenced by the main gas isotope, an effect of the ion mass in agreement with the experimental (so called anti-gyro-Bohm) scaling is revealed in the low wavenumber range. In this context, the major role played by the E × B shear in regulating the ion-temperature-gradient turbulence is analyzed in some detail. The competing level of turbulent and neoclassical transport is quantified to shed light on the experimental features of the pedestal profiles at different ion mass, with the particle transport found to be consistent with a higher pedestal top density for increasing isotope masses, and the heat transport shown to match the roughly unaltered observed temperature profiles.